Analysis of the degradation of BaTiO3 resistivity due to hydrogen ion incorporation: Impedance spectroscopy and diffusion analysis. (1st September 2015) - Sohrabi Baba Heidary, Damoon; Randall, Clive A.
Abstract: The resistivity of insulator oxide materials can be compromised when they are exposed to hydrogen gas at high temperatures, as insulation resistance can significantly decrease. In this study, we differentiate between electrode, grain boundary, and grain contributions to total resistivity by impedance spectroscopy (IS) tests and a 3RC model. It turns out that the largest contribution to total resistivity comes from electrode Schottky barriers, which control the major part of the degradation. Based on the IS analysis, the hydrogen diffusion coefficients of those three components were successfully calculated and compared with the diffusion coefficient in other systems. Determination of the hydrogen diffusion in grains and grain boundaries is important in understanding how hydrogen penetrates to capacitors and can also be useful for applications that involve extreme environments. In this study, we also considered the kinetics and role of the metal electrode chemistry (Ag, Au, and Pt) and the thickness of active layers on the hydrogen degradation.